Collaborative Action Research in a Northern Early Childhood Educator Program: Professional Learning of Instructors and Interns - McDonald, Erica; Simpson, Charlene; McGregor, Sarah; Peterson, Shelley Stagg; Eisazadeh, Nazila (The Canadian Journal of Action Research)

(untitled) (Canadian Association of Action Research in Education, 2024)
This collaborative action research, carried out by early childhood education interns, with the support of their instructor and two university researchers, shows the empowerment of postsecondary students that occurs when they are responsible for designing and implementing research projects tailored to their placement contexts. The early childhood educator interns took up a stance as reflective practitioners who developed professional skills and knowledge in an area that was meaningful to them—teaching young children their Indigenous language. The interns shared responsibility for their learning with their instructor, who was also conducting research into her practice, gathering data to identify the impact of her new teaching approach on interns’ learning. The simultaneous use of collaborative action research methods at the instructor and intern levels provides research-based information for the larger professional field. Additionally, the college instructor and the student interns are positioned as research-practitioners who use action research to support their professional growth.